Faktor-Faktor Yang Berhubungan Dengan Persalinan Preterm Pada Ibu Bersalin Di RSUD Pariaman Tahun 2023 - Nela Novita Sari (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
According to WHO preterm birth is the birth of a fetus between 20-37 weeks of gestation. Pretem babies have a higher risk of death, infection, disability in terms of long term, cognitive, visual, hearing, attitude, social emotional, health and growth problems. According to the central statistics agency through the indonesian demographic and health survey in 2021, the infant mortality rate in indonesia is 34/1000 live births. Based on this, it can be seen that premature birth is still a problem with the incidence rate increasig from year to year, for this reason the author is interested in concting this research . the aim of this research is to determine maternal factors that cause the incidence of premature RSUD Pariaman 2023. this research was carried outusing a retrospective methode using a case control approach. Based on the results, it was found that mothers had an age at risk of 63,0 then by a parity at risk of 56,5 and 75,8 of placenta previa was 0,038 and 0,002<0,05, there is a relationship between age and placenta previa and preterm birth prever to p value of0,286>0,05 there is not relationship between parity and preterm birth. In conclution there is a relationship between age and placenta previa with preterm birth. Researches to use other variable related to preterm birth.